The Role of Buddhist Religious Education in Strengthening Morality and Ethics at The Institute of Business, Information Technology, and Management - Albert Albert; Jacqueline Jacqueline; Stevannie Djohan; Jennifer Lim; Irvan Jawari (Utan Kayu Publishing, 2025)
This study aims to examine the extent to which Buddhist religious education contributes to strengthening the moral and ethical character of students at the Institute of Business, Information Technology, and Management. Buddhist religious education is viewed as an essential medium for shaping character based on the values of honesty, responsibility, discipline, and empathy.This research employed a pre-test and post-test design. Data were collected through questionnaires and analyzed using SPSS, involving validity and reliability tests, normality and homogeneity tests, correlation analysis, regression analysis, and a Paired Sample t-Test. The mean score increased from 19.06 (pre-test) to 41.60 (post-test), indicating an improvement in students’ moral and ethical behaviour after participating in Buddhist religious education. The Paired Sample t-Test results show a Sig. (2-tailed) value of 0.000 ( 0.05), demonstrating a significant difference between pre- and post-learning outcomes. The correlation coefficient (R = 0.944) and the coefficient of determination (R² = 0.890) indicate a very strong relationship, in which 89% of the improvement in students’ moral and ethical development is explained by Buddhist religious education. Thus, Buddhist religious education has been proven to exert a positive and significant influence in shaping morally grounded and ethically responsible student character, thereby supporting the creation of a harmonious and integrity-driven campus environment.